2007
DOI: 10.13181/mji.v16i4.288
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders in elderly patients

Abstract: Hubungan antara tanda dan gejala Temporomandibular Disorders (TMD) dengan usia masih kontroversial. Pada umumnya penelitian mengenai TMD banyak dilakukan pada populasi dewasa, tetapi kurang pada lanjut usia (lansia). Tujuan penelitian adalah untuk mengetahui frekuensi TMD pada lansia dan faktor-faktor risiko yang mempunyai hubungan dengannya. Penelitian potong lintang ini dilakukan pada pasien-pasien lansia yang datang ke Departemen Geriatri Rumah Sakit Umum Pusat Nasional Cipto Mangunkusumo, Jakarta, Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
3
0
4
Order By: Relevance
“…The results study showed that signs and symptoms of temporomandibular joints increased in individuals who had lost more teeth, this result which is in line with study from Himawan [11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results study showed that signs and symptoms of temporomandibular joints increased in individuals who had lost more teeth, this result which is in line with study from Himawan [11].…”
Section: Discussionsupporting
confidence: 88%
“…Occlusal posterior tooth contact serves to maintain maximal mandibular stability and minimize pressure on the tooth so as to enable the jaw to be able to receive heavy loads without disturbing its teeth and supporting structures. Unlike the anterior teeth whose primary purpose is not to maintain the vertical dimension but to serve as the mandibular guidance during anterior mandibular movement [11]. This means that the distribution of missing posterior teeth is more important than missing anterior teeth to have an effect on the incidence of temporomandibular joint disorders but in this study, location of tooth loss is not distinguished.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Keluhan tersebut sering dianggap bukan berasal dari gigi maupun sendi sehingga pasien sering tidak menyadari adanya tanda dan gejala TMD yang dimilikinya (Casanova et al, 2006;Himawan et al, 2007dan Costa et al, 2010 (Nomura et al, 2009). Berdasarkan Grossi et al, 2006;Oliveira et al, 2006;Nomura et al, 2009;Brandini et al, 2012) dan juga untuk menyaring/ skrining pasien dalam rangka mendiagnosis TMD lebih lanjut (Hiltunen, 2003 (Nomura et al, 2009).…”
Section: Pendahuluanunclassified
“…2 Proses degenerasi stomatognatik dalam lansia antara lain hilangnya jumlah gigi anterior maupun posterior akibat kelainan jaringan periodontal atau karies, hiposalivasi, penurunan aktivitas dan massa otot, serta terjadi penurunan fungsi pada temporomandibular joint (TMJ). 3 Hal ini dapat mengakibatkan terjadinya temporomandibular disorder (TMD). 1 Tanda dan gejala utama TMD ialah rasa nyeri pada TMJ, keterbatasan dalam membuka mulut, krepitasi pada saat membuka atau menutup mulut, dan sakit kepala.…”
Section: Pendahuluanunclassified